Penerapan Model Problem Posing dalam Meningkatkan Kemampuan Berfikir Kritis Siswa pada Mata Pelajaran Matematika Kelas V MI Tumbrep Kecamatan Bandar Kabupaten Batang - Kasih Yanti (Lembaga Bale Literasi, 2022)
The purpose of this study was to describe the application of the Problem Posing model in training the critical thinking skills of fifth grade students of MI Islamiyah Tumbrep 01 Bandar District, Batang Regency, (2) to determine the application of the Problem Posing model in training critical thinking skills of fifth grade students of MI Islamiyah Tumbrep 01 Bandar District, District Batang, (3) to find out the solution to the application of the Problem Posing model in training critical thinking skills of fifth grade students of MI Islamiyah Tumbrep 01 Bandar Subdistrict, Batang Regency. This research is a field research with data collection through interview observation and documentation. The sources used are primary data sources and secondary data sources, namely mathematics subject teachers and fifth grade students of MI Islamiyah Tumbrep 01 as well as relevant supporting books. The techniques used in this research are data collection, data presentation and data withdrawal/leverage. The results of this study are about the application of the Problem Posing Model in training students' critical thinking skills in mathematics subjects for class V MI Tumbrep, Bandar District, Batang Regency. The obstacles in this study include (1) there are some children who lack understanding, (2) there are some children who are not focused, (3) there are some children who are shy and quiet, (4) limited time, (5) class fat and solutions to overcome these obstacles include, (1) student readiness in participating in learning activities in class, (2) teacher and parent cooperation, (3) classroom conditioning